Edukasi Pemanfaatan Sampah Organik Rumah Tangga Menjadi Pupuk Organik Cair yang Bernilai Ekonomis - Grace Leonita Tamba; Setiana Nastiti; Ramadhanie Imansyah Sahdan; Baihaqi Baihaqi (CV. ITTC INDONESIA, 2026)
Poor waste management remains a major environmental issue at the community level due to a lack of understanding regarding waste segregation and utilization. This community service aims to increase public awareness and skills in managing organic and inorganic waste as an effort toward economic and environmental empowerment. The methods used in this activity included interactive socialization, training on waste segregation at the source, and hands-on practice in making compost from organic waste and upcycling inorganic waste. The results indicated a significant increase in public knowledge and active participation in sorting waste. Organic waste was successfully diverted into compost useful for household food security, while economically valuable inorganic waste was channeled to waste banks. In conclusion, this socialization and training program is effective in altering community behavior and fostering self-reliance based on sustainable environmental management.